ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Experimental and Numerical Investigations into the Influence of the Process Parameters During the Deep Drawing of Fiber Metal Laminates - Heggemann, Thomas; Sapli, Hüseyin; Homberg, W. (Forming the Future)

Simplified Numerical Calculation of the Isothermal, Three-Dimensional, Non-Newtonian Flow Characteristics of Single-Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

Non-Isothermal Calculation of the Pressure-Throughput-Characteristics of Single Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021 - Working Group Reports

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021

Data Science ab Klasse 5 - Konkrete Unterrichtsvorschläge für künstliche Intelligenz unplugged und Datenbewusstsein - Podworny, Susanne; Höper, Lukas; Fleischer, Yannik; Hüsing, Sven; Schulte, Carsten (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Datenbewusstsein: Aufmerksamkeit für die eigenen Daten - Höper, Lukas; Schulte, Carsten (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Identity in K-12 Computer Education Research: A Systematic Literature Review - Große-Bölting, Gregor; Gerstenberger, Dietrich Karl-Heinz; Gildehaus, Lara; Mühling, Andreas; Schulte, Carsten (ICER 2021: ACM Conference on International Computing Education Research, Virtual Event, USA, August 16-19, 2021)

ITiCSE 2021 recap - Schulte, Carsten; A. Becker, Brett (ACM SIGCSE Bull.)

Joining of Sheet Metal and Thermoplastic Composites Using Injection Riveting - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes

Fügen von thermoplastischen Composites mit Metallteilen durch Spritznieten - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (Joining Plastics)

Influence of Plasmon Resonances and Symmetry Effects on Second Harmonic Generation in WS2–Plasmonic Hybrid Metasurfaces - Spreyer, Florian; Ruppert, Claudia; Georgi, Philip; Zentgraf, Thomas (ACS Nano)
The nonlinear process of second harmonic generation (SHG) in monolayer (1L) transition metal dichalcogenides (TMD), like WS2, strongly depends on the polarization state of the excitation light. By combination of plasmonic nanostructures with 1L-WS2 by transferring it onto a plasmonic nanoantenna array, a hybrid metasurface is realized impacting the polarization dependency of its SHG. Here, we investigate how plasmonic dipole resonances affect the process of SHG in plasmonic–TMD hybrid metasurfaces by nonlinear spectroscopy. We show that the polarization dependency is affected by the lattice structure of plasmonic nanoantenna arrays as well as by the relative orientation between the 1L-WS2 and the individual plasmonic nanoantennas. In addition, such hybrid metasurfaces show SHG in polarization states, where SHG is usually forbidden for either 1L-WS2 or plasmonic nanoantennas. By comparing the SHG in these channels with the SHG generated by the hybrid metasurface components, we detect an enhancement of the SHG signal by a factor of more than 40. Meanwhile, an attenuation of the SHG signal in usually allowed polarization states is observed. Our study provides valuable insight into hybrid systems where symmetries strongly affect the SHG and enable tailored SHG in 1L-WS2 for future applications.

Learning From Revisions: Quality Assessment of Claims in Argumentation at Scale - Skitalinskaya, Gabriella; Klaff, Jonas; Wachsmuth, Henning (Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics)

Learning Flow Scheduling - Hasnain, Asif; Karl, Holger (2021 IEEE 18th Annual Consumer Communications & Networking Conference (CCNC))
Datacenter applications have different resource requirements from network and developing flow scheduling heuristics for every workload is practically infeasible. In this paper, we show that deep reinforcement learning (RL) can be used to efficiently learn flow scheduling policies for different workloads without manual feature engineering. Specifically, we present LFS, which learns to optimize a high-level performance objective, e.g., maximize the number of flow admissions while meeting the deadlines. The LFS scheduler is trained through deep RL to learn a scheduling policy on continuous online flow arrivals. The evaluation results show that the trained LFS scheduler admits 1.05x more flows than the greedy flow scheduling heuristics under varying network load.
Keywords: Flow scheduling; Deadlines; Reinforcement learning

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)

Die Gestaltung des Übergangs zur Weiterführenden Schule – Welche Maßnahmen wurden und werden an Grundschulen in NRW praktiziert? - van Ophuysen, Stefanie; Schürer, Sina; Bloh, Bea (Zeitschrift für Grundschulforschung)
Zusammenfassung Studien zum Übergang von der Grund- in die weiterführende Schule gibt es zu zahlreichen Themen. Wie Grundschulen den Übergang zur weiterführenden Schule gestalten, wurde bislang jedoch kaum erforscht. Auf Basis des Forschungsstands werden relevante Maßnahmen identifiziert. In einer online-Befragung an 106 Grundschulen in Nordrhein-Westfalen wurde erfasst, inwiefern diese Maßnahmen tatsächlich umgesetzt werden und als wie relevant bzw. schwierig ihre Umsetzung erachtet wird. Die Ergebnisse werden verglichen mit Daten einer Studie, die 2002 an 71 Grundschulen durchgeführt wurde. Es zeigt sich eine hohe Stabilität der Gestaltung in den letzten 15 Jahren. Maßnahmen, die auf stufenübergreifender Kooperation basieren, werden heute zwar häufiger praktiziert, stehen aber weiterhin am Ende der Rangreihe.

Die Perspektive von Referendar*innen auf Forschendes Lernen - Homt, Martina; Bloh, Bea

Requirements for Processing High-Strength AlZnMgCu Alloys with PBF-LB/M to Achieve Crack-Free and Dense Parts - Heiland, Steffen; Milkereit, Benjamin; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Keßler, Olaf; Schaper, Mirko (Materials)
Processing aluminum alloys employing powder bed fusion of metals (PBF-LB/M) is becoming more attractive for the industry, especially if lightweight applications are needed. Unfortunately, high-strength aluminum alloys such as AA7075 are prone to hot cracking during PBF-LB/M, as well as welding. Both a large solidification range promoted by the alloying elements zinc and copper and a high thermal gradient accompanied with the manufacturing process conditions lead to or favor hot cracking. In the present study, a simple method for modifying the powder surface with titanium carbide nanoparticles (NPs) as a nucleating agent is aimed. The effect on the microstructure with different amounts of the nucleating agent is shown. For the aluminum alloy 7075 with 2.5 ma% titanium carbide nanoparticles, manufactured via PBF-LB/M, crack-free samples with a refined microstructure having no discernible melt pool boundaries and columnar grains are observed. After using a two-step ageing heat treatment, ultimate tensile strengths up to 465 MPa and an 8.9% elongation at break are achieved. Furthermore, it is demonstrated that not all nanoparticles used remain in the melt pool during PBF-LB/M.
Keywords: grain refinement; crack reduction; laser beam melting; aluminum alloy; titanium carbide; nanoparticle; PBF-LB/M

The Strong Scaling Advantage of FPGAs in HPC for N-body Simulations - Menzel, Johannes; Plessl, Christian; Kenter, Tobias (ACM Transactions on Reconfigurable Technology and Systems)
N-body methods are one of the essential algorithmic building blocks of high-performance and parallel computing. Previous research has shown promising performance for implementing n-body simulations with pairwise force calculations on FPGAs. However, to avoid challenges with accumulation and memory access patterns, the presented designs calculate each pair of forces twice, along with both force sums of the involved particles. Also, they require large problem instances with hundreds of thousands of particles to reach their respective peak performance, limiting the applicability for strong scaling scenarios. This work addresses both issues by presenting a novel FPGA design that uses each calculated force twice and overlaps data transfers and computations in a way that allows to reach peak performance even for small problem instances, outperforming previous single precision results even in double precision, and scaling linearly over multiple interconnected FPGAs. For a comparison across architectures, we provide an equally optimized CPU reference, which for large problems actually achieves higher peak performance per device, however, given the strong scaling advantages of the FPGA design, in parallel setups with few thousand particles per device, the FPGA platform achieves highest performance and power efficiency.

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Chemical Engineering Transactions)

General relationship between salt concentration and x-ray absorption for binary electrolytes - Steinrück, Hans-Georg (AIP Advances)

Arbeitsbuch Judith Kuckart. Erzählen – Theater – Tanz
In diesem Arbeitsbuch werden die Wege der 1959 in Westfalen geborenen und heute v.a. in Berlin lebenden Judith Kuckart zurückverfolgt – und zwar in den Gattungen Prosa, Theater, Hör-Feature und Film sowie im Bereich Tanz: In all diesen Gattungen hat die Künstlerin seit den 1980er Jahren ein umfassendes OEuvre entwickelt. Im vorliegenden Band werden erstmals alle ihre Schaffensbereiche thematisiert und in ihren Zusammenhängen betrachtet. Dies geschieht mittels wissenschaftlicher Essays, künstlerischer und persönlicher Kurzbeiträge sowie ausführlicher Gespräche mit Judith Kuckart. Ihr künstlerisches Leben und Werk wird auf diese Weise in seinen vielfältigen Aspekten erfasst und der wissenschaftlichen und kulturellen Öffentlichkeit präsentiert.
Keywords: Erzählverfahren deutschsprachige Gegenwartsliteratur Tanztheater Westfalen Heimat Hörspiel

Digitale Räume geben und nehmen: Unterrichtsinteraktion in DSH-Kursen während der COVID-19-Pandemie - Drumm, Sandra; Müller, Mareike; Stenzel, Nadja (Informationen Deutsch als Fremdsprache)
Das Auftreten der COVID-19-Pandemie stellt Fremdsprachenkurse vielerorts vor Herausforderungen. Unter Zuhilfenahme diverser digitaler Tools werden nicht nur Lernmaterialien online geteilt, sondern auch die Interaktion zwischen Lehrenden und Lernenden sowie der Lernenden untereinander in den virtuellen Raum verlagert. Qualitative Interviews mit den Beteiligten erfassen, wie diese mit den Herausforderungen videogestützten Sprachunterrichts umgehen und welche Strategien sie wählen, um Sprachenlernen zu ermöglichen. Die Ergebnisse zeigen auf, wo seitens der Kursorganisation und -durchführung Handlungsbedarf besteht. ----- The rise of the COVID-19 pandemic challenges the teaching and learning of foreign languages at many institutions. The implementation of various digital tools aids not only the online sharing of learning materials, but also shifts teacher-learner and learner-learner interaction to the virtual space. Via qualitative interviews, this study examines how both teachers and learners handle the challenges of language instruction based on videoconferences, and what strategies they employ to enable language learning. The results highlight areas in need of improvement in terms of course organization and facilitation.
Keywords: German language courses at university; interaction; digital space; language learning/teaching via videoconference

MLCHECK–Property-Driven Testing of Machine Learning Classifiers - Sharma, Arnab; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille; Wehrheim, Heike (Proceedings of the 20th IEEE International Conference on Machine Learning and Applications (ICMLA))
In recent years, we observe an increasing amount of software with machine learning components being deployed. This poses the question of quality assurance for such components: how can we validate whether specified requirements are fulfilled by a machine learned software? Current testing and verification approaches either focus on a single requirement (e.g., fairness) or specialize on a single type of machine learning model (e.g., neural networks). In this paper, we propose property-driven testing of machine learning models. Our approach MLCheck encompasses (1) a language for property specification, and (2) a technique for systematic test case generation. The specification language is comparable to property-based testing languages. Test case generation employs advanced verification technology for a systematic, property dependent construction of test suites, without additional user supplied generator functions. We evaluate MLCheck using requirements and data sets from three different application areas (software discrimination, learning on knowledge graphs and security). Our evaluation shows that despite its generality MLCheck can even outperform specialised testing approaches while having a comparable runtime

Systematik zum Einstieg in die Plattformökonomie - Drewel, Marvin

Systematik zur Planung des organisationalen Wandels zum Smart Service-Anbieter - Frank, Maximilian

Rahmenwerk zur Planung und Einführung von Systems Engineering und Model-Based Systems Engineering - Bretz, Lukas

Die Anbahnung einer forschenden Grundhaltung im Verlauf des Praxissemesters: Entwicklungsverläufe und Gelingensbedingungen - Homt, Martina; van Ophuysen, Stefanie

Elternsorgen und Kindersorgen während der Corona-Pandemie - Sander, Andreas; van Ophuysen, Stefanie; Schäfer, Laura; Homt, Martina

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Steigerung der Prognosegüte mechanischer Fügeprozesssimulationen durch den Einsatz einer fügespezifischen Reibmodellierung basierend auf einer experimentellen Parametrisierung - Rossel, Moritz Sebastian; Meschut, Gerson (11. Fügetechnisches Gemeinschaftskolloquium)

Motivationsregulationsformen zum Erwerb pädagogisch-psychologischer Theorien und Befunde im Lehramtsstudium - Grosser, Christine; Wehde, Janis

Die Reflexion der eigenen Lehrtätigkeit von Studierenden in Praxisphasen durch Forschendes Lernen: Prädiktiver Einfluss subjektiver Normen im schulischen und universitären Kontext - Wehde, Janis; Bloh, Bea

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Großserientaugliche induktive Platinenerwärmung für den Warmformprozess - Tröster, Thomas; Pfeifer, Florian; Nacke, Bernard; Dietrich, André

Kollektive Reflexionsphasen - Bloh, Thiemo

IT-Systeme für das Krisenmanagement - Pottebaum, Jens; Schäfer, Christina (Sicherheitskritische Mensch-Computer-Interaktion)

Die Zukunft sicherheitskritischer Mensch-Computer-Interaktion - Reuter, Christian; Aal, Konstantin; Beham, Frank; Boden, Alexander; Brauner, Florian; Fiedrich, Frank; Fuchs-Kittowski, Frank; Geisler, Stefan; Gennen, Klaus; Herrmann, Dominik; Kaufhold, Marc-André; Klafft, Michael; et al. (Sicherheitskritische Mensch-Computer-Interaktion)

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)
Um der ansteigenden Erderwärmung entgegenzuwirken, erheben immer mehr Regierungen Steuern und Strafzahlungen auf den CO2-Ausstoß. Dieses betrifft auch die Ersatzteil¬versorgung im Automobilbereich. Dabei muss bislang dem Bedarf vorgelagert produziert werden, was mit hohen Lagerkapazitäten und logistischen Aufwänden verbunden ist. CO2-Einsparungen sind daher durch einen Wechsel auf die additive on-demand-Fertigung über ein dezentrales Fertigungsnetzwerk aus Lohndienstleistern möglich. Allerdings ist die dezentrale Ersatzteilfertigung trotz Einbezug des CO2-Preises nicht in jedem Fall wirtschaftlich. Der Grund hierfür liegt in der Abhängigkeit der Gesamtkosten von Faktoren wie Bauteilgeometrie, Logistikaufwand und Stückzahl. Im vorliegenden Beitrag wird eine Vorgehensweise für den Vergleich einer zentralen mit einer dezentralen Ersatzteilversorgung durch die Ergänzung relevanter, produktspezifischer Kennwerte für die additive Bauteilfertigung beschrieben. Neben der Ökobilanz berücksichtigt die entwickelte Methode die wirtschaftliche Rentabilität des Herstellungsverfahrens. Die Validierung dieser Vorgehensweise erfolgt in Kooperation mit einem deutschen Automobilhersteller. Die entwickelte Vorgehensweise dient Automobilherstellern als Entscheidungsunterstützung bei der Fragestellung, ob einzelne Ersatzteilkomponenten herkömmlich oder additiv gefertigt werden.

Should I stay or should I go? The dark side of corporate entrepreneurship - Tomin, Slawa; Krebs, Benjamin (Frontiers of Entrepreneurship Research)

HRM in the Germanic context - Krebs, Benjamin; Wach, Bernhard Alexander; Wehner, Marius Claus; Reichel, Astrid; Mayrhofer, Wolfgang; Sender, Anna; Staffelbach, Bruno; Ligthart, Paul (Handbook on contextual approaches to human resource management)

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Fluid Dynamics of the Open Port Interface for High-Speed Nanoliter Volume Sampling Mass Spectrometry - Liu, Chang; Van Berkel, Gary J.; Kovarik, Peter; Perot, J. Blair; Inguva, Venkatesh; Covey, Thomas R. (Analytical Chemistry)

Analyzing Approximate Value Iteration Algorithms - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Mathematics of Operations Research (to appear))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)

Deep Q-Learning: Theoretical Insights from an Asymptotic Analysis - Ramaswamy, Arunselvan; Hüllermeier, Eyke (IEEE Transactions on Artificial Intelligence (to appear))